Studies of Northeast Pacific Gracilariaceae. - Dawson, E.Yale (University of Southern California Press, 1949)
contents: Contributions toward a marine flora of the Southern California channel islands, I-III. The marine flora of isla San Benedicto following the volcanic eruption of 1952-1953. Marine algae from Palymra island with special reference to the feeding habits and toxicology of reef fishes